Five-year survey of bird species inventory and distribution in Sanggabuana Mountains, West Java, Indonesia - BERNARDINUS T. WAHYU WIRYANTA; FENI SUGIARTI; ASYSYAMS ANNISA; SITTI BALQIS KHADIJAH; UCE SUKENDAR; YUNUS TRIYONGGO; DELFANIA MATASIK (Society for Indonesian Biodiversity, 2026)
Abstract. Wiryanta BTW, Sugiarti F, Annisa A, Khadijah SB, Sukendar U, Triyonggo Y, Matasik D. 2026. Five-year survey of bird species inventory and distribution in Sanggabuana Mountains, West Java, Indonesia. Biodiversitas 27 (6): d270605. https://doi.org/10.13057/biodiv/d270605. The Sanggabuana Mountains in West Java are a tropical forest area of substantial ecological importance, yet information on bird diversity in this region remains limited. This study aims to document bird species diversity, taxonomic composition, feeding guild proportions, spatial distribution patterns, and the conservation status of birds as a basis for conservation planning in the Sanggabuana Mountains. This study presents one of the first baseline inventories of bird species conducted during the 2021-2025 period using a combination of line transect and point count methods. In total, 176 bird species were recorded, representing 57 families and 18 orders, with the order Passeriformes being the dominant group. A diversity index value of 1.84 indicates a moderate level of taxonomic composition. Additionally, the presence of four migratory bird species highlights the importance of this area as a tropical forest habitat and a regional migration stopover site. Based on spatial analysis using the average nearest neighbor (ANN) method, species distribution patterns tend to be clustered, although some feeding guilds exhibit random distribution patterns. A total of 13 species are classified as threatened according to the International Union for Conservation of Nature (IUCN), comprising three critically endangered, five endangered, and five vulnerable species. Based on regional distribution data, 98.29% of the recorded species are known to occur in Java. These results provide relevant basic ecological information to support long-term biodiversity monitoring efforts and serve as a foundation for developing conservation strategies in the Sanggabuana Mountains.